2018
DOI: 10.31234/osf.io/ygrh3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Cognitive and Academic Benefits of Cogmed: A Meta-Analysis

Abstract: Cogmed Working Memory Training (CWMT) is a commercial cognitive-training program designed to foster working-memory capacity. Enhanced working-memory capacity is then supposed to increase one’s overall cognitive function and academic achievement. This meta-analysis investigates the effects of CWMT on cognitive and academic outcomes. The inclusion criteria were met by 50 studies (637 effect sizes).Highly consistent near-zero effects were estimated in far-transfer measures of cognitive ability (e.g., attention an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 37 publications
2
14
1
Order By: Relevance
“…None of these untrained functions were improved by BrainGame Brian training either. Our results are also in line with previous meta-analyses investigating the effect of CWMT on far transfer measures in children with ADHD [41,42,73,74]. Despite the behavioral parallels between ADHD and symptoms of inattention in children born very preterm, the neurobiological underpinnings of these symptoms may actually be different.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…None of these untrained functions were improved by BrainGame Brian training either. Our results are also in line with previous meta-analyses investigating the effect of CWMT on far transfer measures in children with ADHD [41,42,73,74]. Despite the behavioral parallels between ADHD and symptoms of inattention in children born very preterm, the neurobiological underpinnings of these symptoms may actually be different.…”
Section: Discussionsupporting
confidence: 89%
“…Cogmed Working Memory Training (CWMT) is widely used in children with Attention Deficit/Hyperactivity Disorder (ADHD) [40]. It has been coined as a promising computerized EF training for attentional problems [41], although more recent studies suggest that it might not be as effective as previously thought [42]. In very preterm children, a recent randomized controlled trial showed no effects of CWMT on any outcome measure, including attentional functioning [43].…”
Section: Introductionmentioning
confidence: 99%
“…Several cognitive training methods for young adults have been reported, such as working memory training [ 1 ], processing speed training [ 2 ], and a braining training game such as Brain Age [ 3 ]. A recent meta-analysis [ 4 ] and second-order-meta-analysis [ 5 ] have reported small positive effects on specific cognitive functions after cognitive training if mental processes are similar between the training task and a cognitive functions measure (near transfer). For example, working memory training has positive effects on working memory performance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous evidence suggests that WM training can improve performance on untrained WM tasks ("near-transfer effects"). However, the question of whether training-induced improvements in WM capacity lead to improvements in other important skills, such as academic and self-regulation skills ("far-transfer effects"), lacks a conclusive answer, as even meta-analyses and review studies are controversial on this point (Shipstead, Hicks and Engle 2012;Karbach and Verhaeghen 2014;Au et al 2015; Melby-Lervag, Redick and Hulme 2016;Aksayli, Sala and Gobet 2019;Sala et al 2019).…”
Section: Introductionmentioning
confidence: 99%